Organizational Citizenship Behavior (OCB) In Achieving Police Organization Goals - Annisa Asri Aprillia; Chairul Muriman Setyabudi; Surya Nita (Budapest International Research and Critics University, 2022)
Police are an organization that is different from the organization in general and has a goal to maintain security and order in society. This shows different organizational contexts and makes measuring OCB in these organizations different. This paper aims to analyze the implementation of organizational citizenship behavior in fulfilling the duties of the police organization to maintain security and public order. Descriptive qualitative method with a literature review approach was used in this study. Literature review was conducted on articles, journals and books related to the research problem. The findings show that OCB is generally shown by the attitudes of employees who try to do more than their formal duties. Managers can then observe it from several OCB dimensions that employees may exhibit or use the same dimension to measure OCB in an employee. However, because police organizations are different from organizations in general, OCB in police organizations can be measured by four dimensions, namely organizational loyalty, service delivery, altruism, and compliance. The implication for police managers is that this can be used to develop OCB in the police force and used to assess the extent to which police officers apply OCB, including the use of discretion in providing justice in their daily duties.